Gender differences in reasons for alcohol and drug abuse among youth in Kenya: programs for prevention - Kimunya, Faith Wanjiru (AUC Knowledge Fountain, 2012)
Much of the research on alcohol and drug abuse prevention examines general risk and protective factors without considering gender and is conducted primarily in Western cultural contexts. However, gender and culture are important to consider in the design and implementation of alcohol and drug abuse prevention programs because both gender and culture can play a role in the development of risk and protective factors. In order to assess the role that gender and culture might play in alcohol and drug abuse, a literature review was conducted. The literature review focused on the gender differences in reasons for alcohol and drug abuse and analyzed the differences and similarities between Western and African populations. The information gathered was then used to assess existing evidence-based substance abuse prevention programs listed in registries. These programs were examined to determine which risk and protective factors they address, and given gender and cultural differences in alcohol and drug abuse, whether these programs are likely to be effective for men and women across cultures. Finally, the prevention programs identified, using specific criteria, as being most suitable for adaptation in Kenya were selected and a website was created for disseminating culturally appropriate best practices.